Shared care in the follow-up of early-stage melanoma: a qualitative study of Australian melanoma clinicians' perspectives and models of care - Rychetnik Lucie; Morton Rachael L; McCaffery Kirsten; Thompson John F; Menzies Scott W; Irwig Les (BMC, 2012)
Abstract Background Patients with early stage melanoma have high survival rates but require long-term follow-up to detect recurrences and/or new primary tumours. Shared care between melanoma specialists and general practitioners is an increasingly important approach to meeting the needs of a growing population of melanoma survivors. Methods In-depth qualitative study based on semi-structured interviews with 16 clinicians (surgical oncologists, dermatologists and melanoma unit GPs) who conduct post-treatment follow-up at two of Australia's largest specialist referral melanoma treatment and diagnosis units. Interviews were recorded, transcribed and analysed to identify approaches to shared care in follow-up, variations in practice, and explanations of these. Results Melanoma unit clinicians utilised shared care in the follow-up of patients with early stage melanoma. Schedules were determined by patients' clinical risk profiles. Final arrangements for delivery of those schedules (by whom and where) were influenced by additional psychosocial, professional and organizational considerations. Four models of shared care were described: (a) surgical oncologist alternating with dermatologist (in-house or local to patient); (b) melanoma unit dermatologist and other local doctor (e.g. family physician); (c) surgical oncologist and local doctor; or (d) melanoma physician and local doctor. Conclusions These models of shared care offer alternative solutions to managing the requirements for long-term follow-up of a growing number of patients with stage I/II melanoma, and warrant further comparative evaluation of outcomes in clinical trials, with detailed cost/benefit analyses.